2010
DOI: 10.1159/000320271
|View full text |Cite
|
Sign up to set email alerts
|

β-Globin Gene Cluster Haplotypes in a Cohort of 221 Children with Sickle Cell Anemia or Sβ⁰-Thalassemia and Their Association with Clinical and Hematological Features

Abstract: Background/Aims: βS-Haplotype prevalence and its associations with clinical and hematological characteristics were assessed in Brazilian children with sickle cell anemia or Sβ⁰-thalassemia. Methods: A retrospective randomized cohort study was undertaken with 208 SS and 13 Sβ⁰-thalassemia children derived from the Newborn Screening Program of the state of Minas Gerais. βS-Haplotypes were determined by PCR-RFLP. Results: Thirty-nine percent of the SS subjects had the CAR/CAR genotype, 33% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 79 publications
7
20
1
Order By: Relevance
“…Therefore, the study population consisted of 221 children, 208 carrying Hb SS and 13 with Hb S-β 0 -thal. The prevalence of the Bantu or Central African Republic (CAR), Benin, Arabian Indian and atypical haplotype alleles in the 208 Hb SS children was 0.57, 0.42, 0.005, and 0.01, respectively (28).…”
Section: Study Population and Selection Methodologymentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the study population consisted of 221 children, 208 carrying Hb SS and 13 with Hb S-β 0 -thal. The prevalence of the Bantu or Central African Republic (CAR), Benin, Arabian Indian and atypical haplotype alleles in the 208 Hb SS children was 0.57, 0.42, 0.005, and 0.01, respectively (28).…”
Section: Study Population and Selection Methodologymentioning
confidence: 98%
“…The selection methodology of study populations has been described previously (28). Briefly, from about 1.2 million children born between January 1 1999 and December 31 2006, 864 were diagnosed with sickle cell disease at the NSP-MG and scheduled for their first clinical appointment in the outpatient care unit of the HEMOMINAS Foundation (Hemoceter of Minas Gerais) in Belo Horizonte, state of Minas Gerais, Brazil.…”
Section: Study Population and Selection Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the data regarding β S -haplotypes were analyzed in several ways, and none showed a significant association between haplotypes and CVD 3 . The only current evidence on the association between β S -haplotypes and SCA phenotype is their relationship to the level of Hb F. However, the Hb F concentration seems to have no association with CVD 5 .…”
mentioning
confidence: 85%
“…Recently, Filho et al found that Bantu/Atypical β S -globin gene cluster haplotype (β S -haplotype) was associated with the occurrence of CVD, and alpha-thalassemia (α-thal) was not 2 . We also have studied the influence of β S -haplotype and α-thal on CVD in a cohort of 208 children with SCA from Minas Gerais state, Brazil, and published it in 2010 3,4 . In our experience, α-thal genotypes were significantly associated with reduction in CVD risk 4 .…”
mentioning
confidence: 99%